2021
DOI: 10.1093/brain/awab272
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and longitudinal cognitive performance in preclinical and early symptomatic Alzheimer’s disease

Abstract: Sleep monitoring may provide markers for future Alzheimer’s disease; however, the relationship between sleep and cognitive function in preclinical and early symptomatic Alzheimer’s disease is not well understood. Multiple studies have associated short and long sleep times with future cognitive impairment. Since sleep and the risk of Alzheimer’s disease change with age, a greater understanding of how the relationship between sleep and cognition changes over time is needed. In this study, we hypothesized that lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 66 publications
7
51
4
Order By: Relevance
“…A recent study with sleep duration measured by polysomnography also supported our results (37). Lucey et al investigated the relationship between cognitive performance and sleep duration measured by the single-channel EEG device, and showed that individuals with sleeping less than 4.5 or more than 6.5 h at night had declined cognitive scores (37). Because the sleep time is about one hour shorter measured by EEG than by self-reported, the results corresponded to 5.5-7.5 h per night of self-reported sleep time to have the lowest risk (34,37).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A recent study with sleep duration measured by polysomnography also supported our results (37). Lucey et al investigated the relationship between cognitive performance and sleep duration measured by the single-channel EEG device, and showed that individuals with sleeping less than 4.5 or more than 6.5 h at night had declined cognitive scores (37). Because the sleep time is about one hour shorter measured by EEG than by self-reported, the results corresponded to 5.5-7.5 h per night of self-reported sleep time to have the lowest risk (34,37).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, we recommended 7–8 h for total sleep or 6–7 h for nocturnal sleep per day, because such sleep durations had the lowest risk of cognitive impairment. A recent study with sleep duration measured by polysomnography also supported our results ( 37 ). Lucey et al investigated the relationship between cognitive performance and sleep duration measured by the single-channel EEG device, and showed that individuals with sleeping less than 4.5 or more than 6.5 h at night had declined cognitive scores ( 37 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Treating NREM sleep as a continuum instead of discrete stages has been advocated 46 and tested out in a recent clinical trial. 50 This approach has also been used in studies involving acoustic stimulation to boost slow oscillations. 51 Recent observations concerning heart rate changes in response to slow oscillations and sigma activity (in the frequency of sleep spindles) also motivate removal of the artificial boundary in NREM sleep classification.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of sleep accelerates AD progression not only by emotionally affecting the mental states of patients but also through the pathological changes of AD ( Irwin and Vitiello, 2019 ; Van Egroo et al, 2019 ; Wang and Holtzman, 2020 ). Sleep disorders and AD partially share pathological mechanisms and induce similar cognitive deficits ( Uddin et al, 2020 ; Lucey et al, 2021 ). Therefore, it is important to further characterize the possible neuropathological changes of sleep disturbance linked to AD.…”
Section: Introduction To Sleep Disturbance and Alzheimer’s Diseasementioning
confidence: 99%